2020
DOI: 10.1111/jfb.14276
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis provides insights into species distribution and population structure in East Atlantic horse mackerel (Trachurus trachurus and T. capensis)

Abstract: Two sister species of horse mackerel (Trachurus trachurus and T. capensis) are described that are intensively harvested in East Atlantic waters. To address long‐standing uncertainties as to their respective geographical ranges, overlap and intraspecific population structure this study combined genetic (mitochondrial DNA and microsatellite) analysis and targeted sampling of the hitherto understudied West African coast. mtDNA revealed two reciprocally monophyletic clades corresponding to each species with inters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 75 publications
3
9
0
Order By: Relevance
“…Our genomic analysis indicated low genetic differentiation among horse mackerel populations inhabiting the area from the North Sea to north Africa (Figure 1A), more than 4,000 km of coastline (global mean pool- F ST =0.007, range: 0.001-0.012). This result is in agreement with previous studies using few genetic markers (Cimmaruta et al, 2008; Comesaña et al, 2008; Healey et al, 2020; Kasapidis & Magoulas, 2008), and implies that gene flow is pervasive. We infer that in the horse mackerel, since the larval stage lasts about one month (Rusell, 1976), gene flow could predominantly occur between neighbouring areas through passive transport of pelagic eggs and larvae by ocean currents.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our genomic analysis indicated low genetic differentiation among horse mackerel populations inhabiting the area from the North Sea to north Africa (Figure 1A), more than 4,000 km of coastline (global mean pool- F ST =0.007, range: 0.001-0.012). This result is in agreement with previous studies using few genetic markers (Cimmaruta et al, 2008; Comesaña et al, 2008; Healey et al, 2020; Kasapidis & Magoulas, 2008), and implies that gene flow is pervasive. We infer that in the horse mackerel, since the larval stage lasts about one month (Rusell, 1976), gene flow could predominantly occur between neighbouring areas through passive transport of pelagic eggs and larvae by ocean currents.…”
Section: Discussionsupporting
confidence: 93%
“…Our genomic analysis indicated that very few genetic differences exist between horse mackerel populations inhabiting the vast area from the North Sea to north Africa (Figure 1A), more than 4,000 km of coastline (global mean pool- F ST =0.007, range: 0.001-0.012). This result is in agreement with previous studies using a few genetic markers (Cimmaruta et al, 2008; Comesaña et al, 2008; Healey et al, 2020; Kasapidis & Magoulas, 2008), and implies that gene flow is pervasive. Low genetic differentiation can be explained by minimal barriers to gene flow and large population sizes, commonly observed in migratory marine fish.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Previous studies on the European eel using low-density marker sets ( 6 , 11 15 ) or reduced representation sequencing ( 15 ) found little to no differentiation between geographic areas, consistent with a single panmictic population. However, low genetic differentiation at selectively neutral markers is a common observation in marine species with large geographical ranges and gene flow between subpopulations ( 16 , 17 ), but does not necessarily capture patterns of local adaptation. For example, an early study based on 13 allozyme loci failed to identify genetic differentiation among Atlantic and Baltic herring ( Clupea harengus ) from diverse ecological conditions, and a single panmictic population could not be excluded ( 18 ).…”
mentioning
confidence: 99%